Morphological and Physiological Characteristics of Laminar Cells in the Central Nucleus of the Inferior Colliculus - Wallace, Mark N.; Shackleton, Trevor M.; Palmer, Alan R. (Frontiers in Neural Circuits, 2012)
The central nucleus of the inferior colliculus (IC) is organized into a series of fibro-dendritic laminae, orthogonal to the tonotopic progression. Many neurons have their dendrites confined to one lamina while others have dendrites that cross over a number of laminae. Here, we have used juxtacellular labeling in urethane anesthetized guinea pigs to visualize the cells with biocytin and have analyzed their response properties, in order to try and link their structure and function. Out of a sample of 38 filled cells, 15 had dendrites confined within the fibro-dendritic laminae and in 13 we were also able to reconstruct their local axonal tree. Based on dendritic morphology they were subdivided into flat or less flat; small, medium, or large; elongated or disk-shaped cells. Two of the elongated cells had many dendritic spines while the other cells had few or none. Twelve of the cells had their local axonal tree restricted to the same lamina as their dendrites while one cell had its dendrites in a separate lamina from the axon. The axonal plexus was more extensive (width 0.7–1.4 mm) within the lamina than the dendrites (width generally 0.07–0.53 mm). The intrinsic axons were largely confined to a single lamina within the central nucleus, but at least half the cells also had output axons with two heading for the commissure and five heading into the brachium. We were able to identify similarities in the physiological response profiles of small groups of our filled cells but none appeared to represent a homogeneous morphological cell type. The only common feature of our sample was one of exclusion in that the onset response, a response commonly recorded from IC cells, was never seen in laminar cells, but was in cells with a stellate morphology. Thus cells with laminar dendrites have a wide variety of physiological responses and morphological subtypes, but over 90% have an extensive local axonal tree within their local lamina.